Implementing Portuguese for Speakers of Other Languages in Portugal: The case of immigrant adults with no or low education in any language - Matias, A.R.; Oliveira, Nuno; Ortiz, Alejandra (Colloque Internationale “Sciences Humaines et Sociales, Sciences du Langage : Méthodologies Transversales, 2015)
Courses in Portuguese for Speakers of Other Languages, in particular for adult immigrants, have been steadily expanding in Portugal over the last fifteen years. These programmes aim to promote educational and labour market integration, access to Portuguese nationality, and cognitive development. This paper argues that official Portuguese learning policies have mainly targeted a population with an immigrant background that fails to represent the full range of adult immigrants’ needs. In particular, less educated adult immigrants’ educational needs have been persistently neglected. Considering that, hitherto, approximately 9% of trainees have been adult immigrants with no or little education in any language, this group has not received sufficient attention in policy measures, nor has it been fully accommodated in institutional terms. As a starting point, the paper identifies the place of adult immigrant literacy in international and national discussions. Subsequently, it discusses the main official programmes offering Portuguese for Speakers of Other Languages to adult immigrants. The data from the main programmes was backed up by fieldwork, in particular interviews carried out with teachers and public officials. We conclude by raising certain questions on the barriers and strategies that exist and their impact on adult immigrants with no or little education.